2013
DOI: 10.1002/star.201200240
|View full text |Cite
|
Sign up to set email alerts
|

On the differences in the granular architecture and starch structure between pericarp and endosperm wheat starches

Abstract: In this study, the granular organization and structure of transitory starch from wheat pericarp was analyzed and compared to the storage starch from endosperm. Pericarp starch (PS) granules were small and spherical with fuzzy blocklets on the surface. Both starches possessed A-type crystallinity, but the relative crystallinity and the stability of crystals were higher in PS. Iodine absorption was low in PS, but iodine slightly increased the crystallinity. PS had 14% AAM compared to 33% in endosperm starch (ES)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 31 publications
(52 reference statements)
6
24
0
1
Order By: Relevance
“…Blue circles symbolize A-chains, red circles external B-chains, gray circles are glucose residues involved in a branch linkage (arrows), and yellow circles are residues in internal segments of B-chains. Note that the chain segment that carries the reducing end (/) is regarded as an internal segment Bertoft et al (2008) c Kalinga et al (2013) d Hanashiro et al (2002) e Zhu et al (2011a) ECL corresponds rather well to the reported thickness of the crystalline lamellae in starch granules (Table 1.1) (Kiseleva et al 2005;Genkina et al 2007;Koroteeva et al 2007a;Kozlov et al 2007a).…”
Section: Major Chain Categoriessupporting
confidence: 67%
See 2 more Smart Citations
“…Blue circles symbolize A-chains, red circles external B-chains, gray circles are glucose residues involved in a branch linkage (arrows), and yellow circles are residues in internal segments of B-chains. Note that the chain segment that carries the reducing end (/) is regarded as an internal segment Bertoft et al (2008) c Kalinga et al (2013) d Hanashiro et al (2002) e Zhu et al (2011a) ECL corresponds rather well to the reported thickness of the crystalline lamellae in starch granules (Table 1.1) (Kiseleva et al 2005;Genkina et al 2007;Koroteeva et al 2007a;Kozlov et al 2007a).…”
Section: Major Chain Categoriessupporting
confidence: 67%
“…The division was based on a collection of seventeen starches from diverse plant species (Bertoft et al 2008), and some structural characteristics in other samples may overlap between the types. Indeed, Zhu et al (2011a) found that amylopectin in sweet potatoes has a structure that is intermediate to types 2 and 3, and the structure of wheat amylopectin appears to be intermediate between types 1 and 2 (Kalinga et al 2013). Nevertheless, the results so far suggest a common, systematic division of the structure of amylopectins that is ubiquitous among plants with a normal starch anabolism.…”
Section: Internal Unit Chains and Structural Types Of Amylopectinmentioning
confidence: 99%
See 1 more Smart Citation
“…As a single amylopectin molecule only contains a single C-chain, this shows that the length of the C-chain greatly varies between individual molecules. Note: Values represent a summary from the literature [9,[189][190][191][192][193][194]. External chains are defined as segments extending from the outermost branch of a chain to its non-reducing end [195].…”
Section: Chain Categoriesmentioning
confidence: 99%
“…49 It has been established that GBSS1 is responsible for the synthesis of the amylose component in starch granules. 50 A mutation that affects any of the SS enzymes could lead to lower amylopectin content and therefore a higher relative AAM content. Indeed, all mutants had higher AAM content compared with the wild type, and double mutants (ss1-ss2-and ss1-ss3-) had even higher AAM compared to single mutants ( Table 1).…”
Section: Amylose Compositionmentioning
confidence: 99%